Korelasi Tinggi Badan Terhadap Panjang Os. Femur Dan Os. Carpalia Digiti III Pada Mahasiswa - Abu Isa Muhammad Fata Mumtaza; Kumala, Noer; Soekanto, Ayly; Herliana, Olivia (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2026)
Background: Height is one of the important anthropometric parameters in the fields of anatomy, physical anthropology, and forensic identification. Height estimation can be done by measuring certain body segments because there is a proportional relationship between the length of body segments and height. The length of the femur segment and the carpalia digiti III segment are body parts that have the potential to be used to estimate height. The purpose of this study was to analyze the relationship between height and the length of the femur segment and the length of the carpalia digiti III segment in students of the Faculty of Medicine, Wijaya Kusuma University, Surabaya, Class of 2023. The research method used an analytical observational design with a cross-sectional approach. The study sample consisted of 30 students who met the inclusion criteria. Height was measured using a microtomies, while the length of the femur segment and the carpalia digiti III segment was measured using an anthropometric tape. Data analysis was performed using Spearman's correlation test, Pearson's correlation test, and linear regression. The results showed that the average height of students was 163.48 cm, the average length of the femur segment was 46.61 cm, and the average length of the carpalia digiti III segment was 9.62 cm. There is a very strong and significant relationship between femur segment length and height (r = 0.909; p = 0.000), and a strong and significant relationship between carpalia digiti III segment length and height (r = 0.714; p = 0.000). Regression analysis shows that femur segment length is a more dominant predictor of height than carpalia digiti III segment length. Conclusion: Femur segment length and carpalia digiti III segment length are significantly related to height, and femur segment length has greater potential as a prediction of height in the fields of anthropometry and forensics.